Central olfactory processing in patients with disorders of consciousness. (29th November 2015) - Nigri, A.; Ferraro, S.; Bruzzone, M. G.; Nava, S.; D'Incerti, L.; Bertolino, N.; Sattin, D.; Leonardi, M.; Lundström, J. N.; ,
Abstract : Background and purpose: Previous studies have demonstrated that individuals suffering from disorder of consciousness (DOC) maintain some minor neural processing of percepts mediated by senses that early in their pathway intersect the thalamus, a key dysfunctional area in DOC patients. Here the degree of sensory preservation within the olfactory system, a system that lacks an obligatory thalamic relay, and its relationship to the consciousness level in DOC patients of various etiologies was assessed. Methods: Clinical Coma Recovery Scale – Revised (CRS‐R) as well as cerebral responses to odors by means of functional magnetic resonance were obtained in a group of vegetative state/unresponsive wakefulness syndrome ( n = 26) patients, minimally conscious state ( n = 7) patients and healthy controls ( n = 25). Results: A majority of vegetative state/unresponsive wakefulness syndrome patients (58%) and 100% of minimally conscious state patients demonstrated a significant preservation of olfactory neural processing, manifested by activation within the piriform cortex, an area considered as a primary olfactory region. Degree of preservation of olfactory processing differed linearly in line with the patients' etiologies where groups demonstrating greater conscious awareness demonstrated more significant processing. Viewed over all DOC patients, there was a significant negative association between odor‐related activity in the orbitofrontal cortex and CRS‐R scores. Conclusions: It is demonstrated that DOC patients exhibit a significant preservation of olfactory neural processing with a clear relationship to etiopathologies and clinical measures even years after of chronification of DOC.